GROWTH OF Bacillaria sp. AS A PRELIMINARY STEP ON THE METAL TOXICITY TESTING - Br Tarigan, Cresentia Karonina; Budijono, Budijono; M.Hasbi, M.Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTMicroalgae are primary producers for aquatic organisms and have the ability to absorb heavy metals up to a certain concentration. One of the microalgae is Bacillaria sp. This research was conducted to determine the ability of Bacillaria sp. as a biota requirement for heavy metal toxicity tests. Observation of growth of Bacillaria sp. carried out for 17 days in order to see all growth phases of Bacillaria sp. The results of this study indicate that there are 5 life phases of Bacillaria sp. namely the lag phase, acceleration phase, exponential phase, retardation phase and death phase. Bacillaria sp. qualified as test biota for heavy metal toxicity test according to the Asean-Canada Cooperative Program on Marine Science Phase II. The cell density of Bacillaria sp. on day 4 or at the beginning of the exponential phase is 1.36 x 106 cells/ml it can be seen that the cell density of Bacillaria sp. exceeds the minimum limit (1x106 cells/ml).Keywords:Bacillaria sp., Exponential, Density, Phytoplankton, Toxicity test